Holding Science Olympiads and Competitions in the Southern Regions During the Years of Independence - Sharopova Nigora Akbarovna (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This study aims to analyze the role of academic olympiads in improving student achievement and developing gifted education in the post-independence period. The research examines the impact of science competitions on students’ academic motivation, intellectual development, and national education quality. A descriptive qualitative method was applied through analysis of educational policy documents, competition reports, and secondary statistical data from national and international sources. The results indicate that academic olympiads contribute significantly to identifying talented students, enhancing problem-solving skills, and increasing international competitiveness. However, disparities in access, teacher preparation, and regional support remain key challenges. The study concludes that strengthening institutional support and inclusive talent development policies is essential for maximizing the educational benefits of academic olympiads.